Transport of Anthocyanins and other Flavonoids by the Arabidopsis ATP-Binding Cassette Transporter AtABCC2 - Behrens, Claire E.; Smith, Kaila E.; Iancu, Cristina V.; Choe, Jun-Yong; Dean, John V. (My University, 2019)
Flavonoids have important developmental, physiological, and ecological roles in plants and are primarily stored in the large central vacuole. Here we show that both an ATP-binding cassette (ABC) transporter(s) and an H+-antiporter(s) are involved in the uptake of cyanidin 3-O-glucoside (C3G) by Arabidopsis vacuolar membrane-enriched vesicles. We also demonstrate that vesicles isolated from yeast expressing the ABC protein AtABCC2 are capable of MgATP-dependent uptake of C3G and other anthocyanins. The uptake of C3G by AtABCC2 depended on the co-transport of glutathione (GSH). C3G was not altered during transport and a GSH conjugate was not formed. Vesicles from yeast expressing AtABCC2 also transported flavone and flavonol glucosides. We performed ligand docking studies to a homology model of AtABCC2 and probed the putative binding sites of C3G and GSH through site-directed mutagenesis and functional studies. These studies identified residues important for substrate recognition and transport activity in AtABCC2, and suggest that C3G and GSH bind closely, mutually enhancing each other’s binding. In conclusion, we suggest that AtABCC2 along with possibly other ABCC proteins are involved in the vacuolar transport of anthocyanins and other flavonoids in the vegetative tissue of Arabidopsis.